Perencanaan Pembangkit Listrik Tenaga Surya On Grid di Desa Porto, Kabupaten Maluku Tengah - Lory Marcus Parera; Boby Kainama (JURNAL SIMETRIK, 2026)
Solar energy is a promising renewable energy source for development, particularly through grid-connected solar power plant systems. This study aims to analyze the potential and design a grid-connected system to efficiently meet electricity needs. The methodology employed includes system capacity design, component selection, and performance simulation using PVSyst software. The design and simulation results indicate that a 135 kWp solar power plant system can generate 214.6 MWh of energy per year with a Performance Ratio (PR) of 84.88%. This PR achievement indicates an excellent level of system efficiency in converting solar energy into electricity that is fed into the grid. Thus, the designed grid-connected solar power system is feasible for implementation and contributes significantly to the provision of clean energy and the reduction of carbon emissions. Keywords: On-Grid PLTS, Pvsyst, Performance Ratio